Feasibility and acceptability of CBT-based group therapy for male victims of child abuse - Gylfi Hvannberg 1992- (2022)
The consequences of a child being abused can be severe and long-lasting. Research have found that adult survivors of child abuse are at more risk of having lower levels of education, less employment, and poorer mental health when compared to adults who have not experienced child abuse. This study tested the feasibility and acceptability of the Recovering from Child Abuse Programme (RCAP) group treatment for adult males’ participants in Iceland. The participants in this study were four Icelandic-speaking men, aged 30 to 54, with a history of childhood abuse, who were seeking help at the Vocational Rehabilitation Fund (VIRK). A thematic framework analysis (TFA) and a visual inspection of the data was performed to answer the research questions which asked: is RCAP 1) feasible in terms of recruitment and attendance, and 2) acceptable for Icelandic-speaking male victims of child abuse in Iceland. The results of the study give some indication that RCAP is feasible and acceptable for this population. In terms of recruitment only five participants took part in the intake interview when there was room for ten applicants, which indicates there could be barriers for men to seek this treatment and should be researched further. Additional research on the effectiveness of the treatment should be considered, as should the feasibility and acceptability for this population with more participants. Several limitations affected this study. The biggest limitations were that the sample in the study was small, and one participant repeatedly gave the same answer, making his answers invalid.